If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 5q = -6 Solving 2p + 5q = -6 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5q' to each side of the equation. 2p + 5q + -5q = -6 + -5q Combine like terms: 5q + -5q = 0 2p + 0 = -6 + -5q 2p = -6 + -5q Divide each side by '2'. p = -3 + -2.5q Simplifying p = -3 + -2.5q
| x-4x+2=11 | | V=6u | | 4*18-t=9 | | (2x-10)(3x+1)=0 | | 1/5x+3=4 | | -3n^4-36n^3-108n^2=0 | | 2(8-x)+2(x-1)=4(x+2)-8 | | 3a^2-18a-120=0 | | 5n-26=18n | | 3x^2=20x+4x^2 | | sqrt(4x-1)+3=0 | | 3(m-3)=4(m+3) | | 9-5x=-30 | | (10/x)=35/(x-5) | | 10/x=35/(x-5) | | 9x+7y=50 | | -3b+5b+7=-9 | | 93.96=4.7+8.7p-2.6p | | 4(7x-8)=-4 | | x-8x=49 | | 5/4m=1/4 | | 5y+6=35 | | x+11/x^2-49x | | 1/3=5/7+y | | 13+7(2x+1)=4x+10 | | 6(-6x-7)=138 | | 4/7n=12 | | -6(4+6x)=-276 | | 5/6t=15 | | 5(x+2)=-12 | | 7(6+4x)=322 | | 4x+3=2x-7+x |